Religion, Science, And Culture Amidst the Covid-19 Pandemic: Muhammadiyah’s Worship Guidance and Members’ Responses - Ahmad Muttaqin (Al-Albab, 2021)
How have religious organizations responded to the COVID-19 pandemic? Why have some religious organizations responded to this outbreak from a scientific perspective, but many others have not? This paper explores the Muhammadiyah's proactive role in responding to the COVID-19 outbreak through an integration-interconnection perspective of religion, science, and culture. Apart from establishing the Muhammadiyah COVID-19 Command Center (MCCC), Muhammadiyah have been actively providing religious guidance amidst the pandemic. Through a review of organizational documents and an auto-nethnography study of the responses of Muhammadiyah members and their community, this paper examines the content and process of disseminating religious guidance, as well as the responses of the organization members and society generally. The dynamics of the response of Muhammadiyah members and sympathizers to religious guidance issued by the Central Board of Muhammadiyah will be read from the perspective of the religious authority in the VUCA (Volatility, Uncertainty, Complexity, Ambiguity) era. This paper underlines that the Muhammadiyah have shown efforts to integrate religion, science, and culture through MCCC to deal with the outbreak. This confirms that the Muhammadiyah movement is both rational and pro-science and serves as a shred of evidence that religious organizations can be problem solvers, although authorities are potentially challenged in the VUCA era.